Assessment of appropriate laboratory measurements to supplement the Crohn's disease activity index. Issue 7 (July 1981) - Andre, C; Descos, L; Landais, P; Fermanian, J
Abstract : The ability of 11 laboratory parameters to reflect the degree of activity of Crohn's disease, using a clinical index as reference point was compared by means of multiple stepwise regression analysis. Activity was best defined in decreasing order by orosomucoid, sedimentation rate, C reactive protein, alpha-1-antitrypsin, albumin, haematocrit, IgM, circulating immune complexes, serum iron, IgG, and IgA. The haematocrit, the only laboratory measurement in the Crohn's disease activity index developed by the National Cooperative Study Group in the USA, is less discriminant than acute phase reactants. Only three parameters-namely, orosomucoid, sedimentation rate, and C reactive protein-have a significant weight and should be complementary to a simple clinical index.